Analysis of deep sequencing exosome‐microRNA expression profile derived from CP‐II reveals potential role of gga‐miRNA‐451 in inflammation - Zhao, Yabo; Fu, Yali; Zou, Mengyun; Sun, Yingfei; Yin, Xun; Niu, Lumeng; Gong, Yanzhang; Peng, Xiuli (Journal of cellular and molecular medicine, 2020)
Mycoplasma gallisepticum (MG) can cause chronic respiratory disease (CRD) in chickens. While several studies have reported the inflammatory functions of microRNAs during MG infection, the mechanism by which exosomal miRNAs regulate MG‐induced inflammation remains to be elucidated. The expression of exosome‐microRNA derived from MG‐infected chicken type II pneumocytes (CP‐II) was screened, and the target genes and function of differentially expressed miRNAs (DEGs) were predicted. To verify the role of exosomal gga‐miR‐451, Western blot, ELISA and RT‐qPCR were used in this study. The results showed that a total of 722 miRNAs were identified from the two exosomal small RNA (sRNA) libraries, and 30 miRNAs (9 up‐regulated and 21 down‐regulated) were significantly differentially expressed. The target miRNAs were significantly enriched in the treatment group, such as cell cycle, Toll‐like receptor signalling pathway and MAPK signalling pathway. The results have also confirmed that gga‐miR‐451‐absent exosomes derived from MG‐infected CP‐II cells increased inflammatory cytokine production in chicken fibroblast cells (DF‐1), and wild‐type CP‐II cell–derived exosomes displayed protective effects. Collectively, our work suggests that exosomes from MG‐infected CP‐II cells alter the dynamics of the DF‐1 cells, and may contribute to pathology of the MG infection via exosomal gga‐miR‐451 targeting YWHAZ involving in inflammation.